Development Of Computer Ergonomics Risk Assessment (COM-ERA) Tool For Assessing Work-Related Musculoskeletal Disorders (WMSDS) Associated With Computing Tasks - Too, Yi Wei (2018)
The cases of work-related musculoskeletal disorders (WMSDs) among office workers who performing computing task are increasing recently. However, the ergonomics assessment tools developed have limitations in assessing risk factors and associated factors for WMSDs due to computing task workstation. The primary objective of this study was to develop a new ergonomics assessment tool, called as Computer Ergonomics Risk Assessment (COM-ERA) for assessing risk factors associated with WMSDs among computer users. An extensive literature review was performed to identify the risk factors and associated factors for WMSDs in computing task. A focus group discussion among ergonomics experts was conducted to finalize the COM-ERA framework and its scoring system. A case study was carried out to determine the validity of the COM-ERA tool using Nordic Musculoskeletal Questionnaire and quantitative physical tests (biofeedback and hand grip strength). All data were analyzed using Statistical Package for Social Science (SPSS version 13). Statistical analysis associated with Chi-square test shows that there was a good agreement between the COM-ERA tool results with the physical test in the neck (X2 (1, N=10) = 0.023, p = 0.88), shoulder and arm (X2 (1, N=10) = 0.47, p = 0.49), wrist (X2 (1, N=10) = 0.74, p = 0.38), back (X2 (1, N=10) = 1.2, p = 0.26), and leg regions (X2 (1, N=10) = 0.47, p = 0.49). Additionally, a reliability test was conducted by comparing the COM-ERA scores of 20 observers using intra-class correlation (ICC) analysis. The COM-ERA scores exhibited high Intra-observer reliability (ICC = 0.89). This study concluded that the COM-ERA was proven to be a valid and reliable tool for assessing risk factors associated with WMSDs among computer users.